Microbiology of waterborne diseases : microbiological aspects and risks - Percival, Steven L. (Academic Press, 2014)
Provides current knowledge on drinking water pathogens highlighting their microbiology, clinical features, survival in the environment and risk assessment. Describes the diseases associated with water, their causative agents and the ways in which they gain access to water systems.